The 14th colony [large type] - Berry, Steve, 1955- (Berry, Steve, 1955- Cotton Malone novels., 2016)
Shot down over Siberia in what was to be a simple meet-and-greet-mission, ex-Justice Department agent Cotton Malone is forced into a fight for survival against Aleksandr Zorin, whose loyalty to the former Soviet Union has festered for decades into an intense hatred of the United States. Before escaping, Malone learns that Zorin and another ex-KGB officer, this one a sleeper still imbedded in the West, are headed overseas to Washington D.C. Inauguration Day -- noon on January 20th -- is only hours away. A flaw in the Constitution, and an even more flawed presidential succession act, have opened the door to political chaos and Zorin intends to exploit both weaknesses to their fullest. Armed with a weapon leftover from the Cold War, one long thought to be just a myth, Zorin plans to attack. He's aided by a shocking secret hidden in the archives of America's oldest fraternal organization, the Society of Cincinnati, a group that once lent out its military savvy to presidents, including helping to formulate three covert invasion plans of Canada. In a race against the clock that starts in the frozen extremes of Russia and ultimately ends at the White House itself, Malone must not only battle Zorin, he must also confront his deepest fear, a crippling weakness that he's long denied but one that now jeopardizes everything.